203 SEPTIC SHOCK AND RECURRENT PNEUMONIA IN A 12-YEAR-OLD BOY WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (10th December 2015) - Geracht, J.; Young, K.; Barron, J.; Epstein, D.
Abstract : A 12-year-old boy with systemic lupus erythematosus and lupus nephritis was admitted to the hospital with his third episode of pneumonia in six weeks. Prior to admission, he had received four courses of cytoxan and had been chronically taking prednisone. Cefotaxime was started on admission, until the second hospital day when a urine culture grew enterococcus. Antibiotic therapy was then changed to vancomycin and gentamicin. On the sixth hospital day, the patient developed septic shock and he was transferred to the pediatric intensive care unit (PICU). A blood culture from admission grew fungus and the enterococcus that grew from the urine proved to be resistant to vancomycin. In the PICU, he had a heart rate of 120 and was tachypneic with a respiratory rate in the 40's. A blood pressure was unable to be obtained. He was lethargic and had poor peripheral perfusion. He was placed on broader spectrum antibiotics and antifungal medications. The patient was subsequently intubated for respiratory failure and received aggressive fluid resuscitation. He required increasing inotropic support, including epinephrine, dopamine, dobutamine, vasopressin, and norepinphrine before a blood pressure of 80's/40's could be obtained. Stress dose steroids were administered. He also received intravenous immunoglobulin. Despite escalating doses of multiple vasopressors, the patient's hemodynamic status continued to deteriorate. The patient suffered a cardiac arrest and was not able to be resuscitated. Two days following his death, Cryptococcus neoformans was identified from the initial blood culture. Cryptococcus neoformans was recovered from the lymph nodes, spleen, and lungs on autopsy. Post-mortem findings also showed a hemorrhagic pneumonitis due to Cryptococcus neoformans.